Effect of subthreshold slope on the sensitivity of nanoribbon sensors. (3rd June 2016) - Sun, K; Zeimpekis, I; Hu, C; Ditshego, N M J; Thomas, O; de Planque, M R R; Chong, H M H; Morgan, H; Ashburn, P
Abstract: In this work, we investigate how the sensitivity of a nanowire or nanoribbon sensor is influenced by the subthreshold slope of the sensing transistor. Polysilicon nanoribbon sensors are fabricated with a wide range of subthreshold slopes and the sensitivity is characterized using pH measurements. It is shown that there is a strong relationship between the sensitivity and the device subthreshold slope. The sensitivity is characterized using the current sensitivity per pH, which is shown to increase from 1.2% ph −1 to 33.6% ph −1 as the subthreshold slope improves from 6.2 V dec −1 to 0.23 V dec −1 respectively. We propose a model that relates current sensitivity per pH to the subthreshold slope of the sensing transistor. The model shows that sensitivity is determined only on the subthreshold slope of the sensing transistor and the choice of gate insulator. The model fully explains the values of current sensitivity per pH for the broad range of subthreshold slopes obtained in our fabricated nanoribbon devices. It is also able to explain values of sensitivity reported in the literature, which range from 2.5% pH −1 to 650% pH −1 for a variety of nanoribbon and nanowire sensors. Furthermore, it shows that aggressive device scaling is not the key to high sensitivity. For the first time, a figure-of-merit is proposed to compare the performance of nanoscale field effect transistor sensors fabricated using different materials and technologies.